(untitled) (Global Journal of Science Frontier Research, 2022)
This article shows how the external gravity force on the core of the planet leads to the appearance of the magnetic field (MF) of the planet. How this force provides acceptable conditions for the existence of life. Natural phenomena, which can easily be explained using the proposed mechanism of interaction of planets, such as earthquakes, mountain formation, ocean currents, tides, time jumps, changes in the duration of the day, periodic Solar activity are considered.